(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Introduction: Osteosarcoma is the most common malignancy of bone. Multi-disciplinary treatment has improved clinical outcomes up to 70%. Factors such as alkaline phosphatase, lactate dehydrogenase, and post-chemotherapy tumor necrosis factor-alpha play a key role in predicting prognosis. However recently, due to cost-effectiveness of inflammatory markers derived from complete blood count have gained popularity in determining survival rates. Methods: The retrospective study was conducted at Children Cancer Hospital/ The Indus Hospital Karachi in pediatric population aged below 18years. 73 patients meeting the inclusion criteria were included in the study who were enrolled from 2005 to 2015. Medical records were reviewed and their survival was analyzed with hematological indices using complete blood count and other medical and surgical variables. Results: Out of these 73 patients, 54.8% were male and survival was found to be 38.4%. The most common site of the presentation was tibia (47.9%). In univariate analysis, pre treatment hemoglobin levels, completion of neoadjuvant therapy and adjuvant therapy, pathological fracture on presentation, metastasis, surgery performed, TLC ?0.6875, NC ?0.471, and LC ?0.2343 were found to be significant risk factors of death. In multivariate analysis metastasis during or after treatment, hemoglobin levels <11mg/dl and TLC ?0.6875 were the found to be the major factors of death. Conclusion: None of the pre-treatment indices taken from CBC proved to predict survival except hemoglobin (<11 mg/dl) and TLC (?0.6875) which were associated with an increased risk of disease progression along with metastasis either during or after treatment